THE EVOLUTION OF ANTHROPOLOGY IN ALGERIA: FROM COLONIAL REJECTION TO CONTEMPORARY RECOGNITION - Bridja Cherifa; Latreche Fairouz (International Journal of Innovative Technologies in Social Science, 2025)
Anthropology was introduced to Algeria through colonial military studies conducted by the French military class. These colonial anthropological studies provided an overview of Algerian society, facilitating the rapid invasion of the region. Consequently, after independence Anthropology was marginalized in Algerian academia and labeled a "colonial science". However, due to changing political, social and cultural conditions Anthropology gradually gained recognition in Algeria. This article examines the historical development of Anthropology in Algeria, focusing on the process of teaching Anthropology and its current status. The research aims to trace the historical trajectory of Anthropology in Algeria and clarify its present status. The methodology of this article includes an introduction, presentation and conclusion. The introduction provides a comprehensive explanation of the topic and its problematic aspects. The presentation is divided into four sections: • The Concepts. • The state of Anthropology in Algeria before and during the colonial period. • The process of teaching Anthropology in post-independence Algeria. • Anthropological studies and research in Algerian academies post-Covid-19. The conclusion presents the findings, highlighting the transformation of anthropology in Algeria into a distinguished and significant field of study.